Wood-plastic from Pennisetum Purpureum Fibers and Recycled Low-density Polyethylene. Issue 3 (4th March 2022) - Grillo, Camila Cezar; Saron, Clodoaldo
ABSTRACT: Natural fibers (NFs) has been an interesting source for reinforcement in polymer composites due to their high availability, low production cost, and satisfactory performance for requirements of the composites, mainly related to the mechanical properties. NFs show remarkable importance for polyolefin recycling since it can improve materials properties that are depreciated due to the contamination or degradation of the polymeric waste. Moreover, polyolefins such as low-density polyethylene (LDPE) are processed at relatively low temperature that allows the incorporation of the NFs in the polymeric matrix by thermomechanical processing, generating products such as wood- plastic composites (WPCs). In present study, the aim was to produce fibers from Pennisetum purpureum for incorporation in LDPE waste, generating WPCs. P. purpureum was easily processed by operations of milling and sieving, producing considerable reinforcement in composites of LDPE. WPCs from P. purpureum and LDPE have presented satisfactory thermal, mechanical, and flow properties. Thus, it shows high potential for LDPE waste recycling.